Good Intentions OverRuled : a Critique of Empowerment in the Routine Organization of Mental Health Services. - Townsend, Elizabeth (University of Toronto Press, 1998)
Townsend illustrates how attempts by occupational therapists to enable empowerment in everyday practice are thwarted by the institutional processes of admission, accountability, decision making, budgeting, risk management, and discharge.